2021
DOI: 10.1002/gepi.22421
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide association analysis of COVID‐19 mortality risk in SARS‐CoV‐2 genomes identifies mutation in the SARS‐CoV‐2 spike protein that colocalizes with P.1 of the Brazilian strain

Abstract: SARS‐CoV‐2 mortality has been extensively studied in relation to host susceptibility. How sequence variations in the SARS‐CoV‐2 genome affect pathogenicity is poorly understood. Starting in October 2020, using the methodology of genome‐wide association studies (GWAS), we looked at the association between whole‐genome sequencing (WGS) data of the virus and COVID‐19 mortality as a potential method of early identification of highly pathogenic strains to target for containment. Although continuously updating our a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 38 publications
(46 reference statements)
0
23
0
Order By: Relevance
“…RNAs 1b-g are complementary to 1a (Figure 2). All the nucleotides in RNA 1b are canonical, while those in 1c-g include the modified nucleotides Ψ, m 5 C, m 6 A, m 1 A and m 3 C, respectively. Between the RNA extension starting site (nucleotide 21) and the modified nucleotides, four or more canonical nucleotides were placed.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…RNAs 1b-g are complementary to 1a (Figure 2). All the nucleotides in RNA 1b are canonical, while those in 1c-g include the modified nucleotides Ψ, m 5 C, m 6 A, m 1 A and m 3 C, respectively. Between the RNA extension starting site (nucleotide 21) and the modified nucleotides, four or more canonical nucleotides were placed.…”
Section: Resultsmentioning
confidence: 99%
“…[3][4][5] In addition, answers in contexts such as affinity of ACE2 with spike protein and doses of virus exposed have also been suggested. 6 Further, genome wide association studies have been carried out to answer these questions on the ground of genetics. [7][8][9][10] In this paper, we report our studies on the effects of several RNA modifications (Figure 1)pseudouridine (Ψ), 5-methylcytosine (m 5 C), N 6 -methyladenosine (m 6 A), N 1 -methyladenosine (m 1 A), and N 3 -methylcytosine (m 3 C) that can potentially be installed on the SARS-CoV-2 RNA genome by the host epitranscriptomic machineryon the catalytic activity of SARS-CoV-2 replication complex (SC2RC), which includes RNA dependent RNA polymerase (RdRp).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A small number of genomic epidemiologic studies have explored the association of host and pathogen genetic variation and COVID-19 severity [8][9][10][11]. A study by Dite G et al, using UK biobank data, performed a GWAS in the human genome to identify single nucleotide polymorphisms (SNPs) associated with disease severity using a SNP score, as well as the impact of demographic and comorbidity risk factors on severe COVID-19 severity [12].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the Alpha (B.1.1.7) variant has been associated with an increased mortality risk compared to previously circulating variants (Challen et al 2021), while the Omicron (B.1.1.529) variant has been associated with a decreased mortality risk compared to the Delta (B.1.617.2) variant (Nyberg et al 2022). Genome-wide association studies can be used to assess the severity-risk of every observed mutation in the SARS-CoV-2 genome (Hahn et al 2021), but such an approach can lack power when the majority of mutations are at low frequencies and higher frequency variants are grouped into emerging variants that spread through the population.…”
Section: Introductionmentioning
confidence: 99%